Adapt or die? - S. S. Visser; A. H. Nel (AOSIS, 1996)
The worldwide economic recession and the concomitant limited stock of finances have had an influence on the available money of every household and have also inhibited the improvement of socio-economic conditions and medicine. The Reconstruction and Development Programme (RDP) has the objective of improving the living conditions of the people with regard to housing, education, training and health care. The latter seems to be a major problem which has to be addressed with the emphasis on the preventive and promotional aspects of health care. A comprehensive health care system did not come into being properly in the past because of the maldistribution of health care services, personnel and differences in culture and health care beliefs and values. The question that now arises, is how to render a quality health care service within the constraints of inadequate financing and resources. A comprehensive literature study has been done with reference to quality health care and financing followed by a survey of existing health services and finances.